Class, states and international relations : a critical appraisal of Robert Cox and neo-Gramscian theory - Budd, Adrian, 1961- (Routledge innovations in political theory ;, 2013)
"This book provides both an outline and a critique of neo-Gramscian international relations theory, from a Marxist perspective"--